Testing of a predictive risk index for persistent postsurgical pain on patients undergoing total knee arthroplasty: A prospective cohort study - Palanne Riku; Rantasalo Mikko; Vakkuri Anne; Olkkola Klaus T; Vahlberg Tero; Skants Noora (WILEY, 2025)
Background: We investigated whether a universal predictive risk index for persistent postsurgical pain (PPP) is applicable to patients who undergo total knee arthroplasty (TKA).
Methods: In this cohort study, 392 participants of a randomized study investigating the effects of anaesthesia methods and tourniquet use on TKA were divided into low-, moderate-, and high-risk groups for PPP, as suggested in the previous risk index study. Patients reported pain using the Oxford Knee Score pain subscale and Brief Pain Inventory-short form preoperatively and 3 and 12 months postoperatively. We compared the pain scores of the low- to moderate- and high-risk groups at respective time points and investigated changes in pain scores and the prevalence of PPP at 3 and 12 months after surgery.
Results: The high-risk group reported more pain 3 and 12 months after TKA than the low- to moderate-risk group. However, of seven variables, only a single difference reached the threshold for minimal clinical importance between the groups at 12 months. Additionally, at 12 months, the low- to moderate-risk group reported slightly worse improvements in three of seven pain variables than the high-risk group. Depending on the definition, the prevalence of PPP ranged from 2% to 29% in the low- to moderate-risk group and 4% to 41% in the high-risk group 12 months postoperatively.
Conclusions: Although the investigated risk index might predict clinically important differences in PPP between the risk groups at 3 months after TKA, it seems poorly applicable for predicting PPP at 12 months after TKA.
Significance: Although many risk factors for persistent postsurgical pain after total knee arthroplasty have been identified, predicting the risk of this pain has remained a challenge. Results of the current study suggest that accumulation of previously presented modifiable risk factors might be associated with increased postsurgical pain at 3 months, but not at 12 months after total knee arthroplasty.